Maximizing Athletic Performance: The Role of Nutrition in Elite Sports - Jia Min Tan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of this research is to determine maximizing athletic performance related to elite sports. Peak performance in professional sports requires more than just tough training; it also involves diligent attention to diet. The Role of Nutrition in Elite Sports" dives at the complex relationship between dietary choices and best athletic results. For measuring, the research study used smart PLS software and generated informative results related to them. Descriptive statistical analysis, and correlation coefficients, also show the smart PLS Algorithm model athletic performance in elite sports. This research focuses on crucial aspects, investigating how macronutrients and micronutrients affect energy metabolism, recovery, and overall physiological resilience. The report also looks at cutting-edge dietary techniques used by elite athletes, with an emphasis on personalized approaches to meet individual demands. Overall, the result found that there are positive and significant relations of maximizing athletic performance in elite sports. As the quest for peak performance grows, this research emphasizes the critical significance of nutrition as a cornerstone in the pursuit of athletic greatness.